α-Glucosidase Inhibition Activity of Stem Bark Ceiba pentandra Linn. In Vitro and In Silico - Syihabudin, Vicri (Indonesian Journal of Pharmacy, 2018)
Ceiba pentandra (L.) stem bark plant contains tannin, flavonoid, alkaloid, terpenoid, and saponin compounds. It is known that flavonoid compounds have a potential for inhibition activity of an α-glucosidase enzyme. The purpose of this research is to know the α-glucosidase inhibition activity of the fraction of n-hexane, ethyl acetate, and water. These three fractions measured α-glucosidase inhibition activity by spectrophotometric UV-vis method. The fraction extract with IC50 values can best be done an analysis of active compounds using LCMS/MS methods, and results of the suspected compound do the binding molecule with a receptor model isomaltase α-glucosidase uses AutoDock Vina so that bond can predict drug active compounds. The results of this research activity are inhibition of α-glucosidase stem bark in the fraction of n-hexane 4,60 μg/mL, ethyl acetate fraction 8,55 μg/mL and fractions of the water 5,61 μg/mL. Analysis of the compound fraction of water by LCMS/MS eluted at the retention time 3,61 seconds allegedly derivative compounds (+) catechin and on retention time 8,70 minutes allegedly derivative compounds vavain. Vavain derivative compounds, (+) catechin, acarbose and quercetin each has its own docking score of -8,1; -8,8; -6,2 and -7,6 kcal/mol and has a semblance of bonding on amino acid Glu276 which is a residue catalytic role in hydrolysis reactions. Equality on the sides of active chemical bonds is expected to have the same activity as drug inhibition of the enzyme α-glucosidase.